Development of Mufradat Quartet Cards for Media Understanding Arabic Sentences - Nab'han Hadyan Adnan; Moh. Khasairi; Moh. Fery Fauzi (PPPBA, 2025)
Arabic which is the language of the Qur'an as well as the language of the Muslim community around the world, is the key to all Islamic knowledge. So the learners of Islam need to learn it. However, most people, especially Islamic learners, think that Arabic is one of the most difficult languages to learn. So this study aims to develop and evaluate the feasibility of mufradat quartet cards as learning media to improve vocabulary understanding and Arabic sentence making skills. The research method used is Al-Hudaiby Research and Development (R&D) model which includes needs analysis, media design, expert validation, revision, field test, and product implementation. The results in the media development process of mufradat quartet cards are equipped with examples of Arabic sentences and their translations. Then the mufradat quartet card media product is very feasible to use as a mufradat learning media. Proven through the validation of the feasibility score of 95% from media experts, 95% from material experts, and 92.85% from teachers. Student responses to this media reached an average of 81.33%, indicating that the mufradat quartet cards are very feasible to use in learning Arabic. The implementation of this media is proven to be effective in improving the understanding of mufradat as well as skills in constructing sentences. This media is expected to contribute significantly to Arabic vocabulary learning.